EVALUASI UJIAN SEKOLAH BERBASIS KOMPUTER (USBK) PENDIDIKAN AGAMA ISLAM TINGKAT SMK TAHUN PELAJARAN 2018/2019 - Bahtian Yusup; Chaerul Rochman; Agus Salim (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
This study aims to evaluate the implementation of Computer-Based School Exams in SMK Negeri 1 Panjalu, this is important to be discussed because for evaluation materials as well as follow-up for the implementation of Computer-Based School Exams especially the subjects of Islamic Education in the coming years can work better. This research method uses participatory descriptive research, Partisifan of this study are the teachers in SMK 1 Panjalu Ciamis. The instrument used refers to the implementation of the Computer Based School Examination (USBK) as a whole in the form of an analysis instrument, and interview guidelines. The conclusion in this study is; (1) Profile of achievement of student learning outcomes in the implementation of Computer-Based School School Exams (USBK) especially Islamic Education subjects where the average score of students is 73.66 and also explained that the average student answers multiple choices of 82 % and answer 18% 2) problems related to the implementation of Computer-Based School School Exams (USBK) both seen in general implementation and related matter questions especially Islamic Education subjects, where the solution in implementing Computer-Based School School Exams (USBK) must be prepared carefully both in terms of the carrying capacity of the facilities and the carrying capacity of human resources, especially teachers because they are related to the application and related to the subject matter of the students, they do not understand the material related to mawaris and the arguments both Al Quran and Hadith, effective and efficient in teaching students about mat eri mawaris.